2017
DOI: 10.1103/physrevb.95.214509
|View full text |Cite
|
Sign up to set email alerts
|

Finite-energy spin fluctuations as a pairing glue in systems with coexisting electron and hole bands

Abstract: We study, within the fluctuation exchange approximation, the spin-fluctuation-mediated superconductivity in Hubbard-type models possessing electron and hole bands, and compare them with a model on a square lattice with a large Fermi surface. In the square lattice model, superconductivity is more enhanced for better nesting for a fixed band filling. By contrast, in the models with electron and hole bands, superconductivity is optimized when the Fermi surface nesting is degraded to some extent, where finite ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 51 publications
0
27
1
Order By: Relevance
“…Such a suppression of T c with greater FeSe-plane separation is observed in metaldoped HfNCl [27]. Recently, Kuroki et al suggested that the superconductivity is optimized when Fermi surface nesting is degraded to some extent [36], which allows finite energy spin fluctuations around the nesting vector to develop. This may explain the existence of an optimum FeSe plane spacing for superconductivity.…”
Section: Discussionmentioning
confidence: 96%
“…Such a suppression of T c with greater FeSe-plane separation is observed in metaldoped HfNCl [27]. Recently, Kuroki et al suggested that the superconductivity is optimized when Fermi surface nesting is degraded to some extent [36], which allows finite energy spin fluctuations around the nesting vector to develop. This may explain the existence of an optimum FeSe plane spacing for superconductivity.…”
Section: Discussionmentioning
confidence: 96%
“…We have found that s±-wave superconductivity is strongly enhanced in the Lieb-lattice model when the d 3z 2 −r 2 band is raised so that it becomes incipient. Such a strong enhancement of s±-wave superconductivity reminds us of the bilayer Hubbard model on a square lattice [39,42,43,[76][77][78][79][80][84][85][86][87][88][89][90][91][92], where enhanced superconductivity is found when one of the bands is incipient [ Hubbard model is a single-orbital (one orbital per site) system with two sites per unit cell. The enhancement of superconductivity in such a system is mediated by spin fluctuations originating from the on-site U , which gives rise to the pairing interaction between the bonding and antibonding bands, both of which have equal weight of the two orbitals in a unit cell.…”
Section: B Relation With the Bilayer Modelmentioning
confidence: 97%
“…Recently, such a band lying just above or below the Fermi level is referred to as an "incipient band" and has received attention, especially in the context of the iron-based superconductors [27][28][29][30][31][32][33][34][35]38], where hole bands lying just below the Fermi level are observed in some materials [30,31,[68][69][70][71][72][73][74][75]. In a wider context, the possibility of the occurrence or strong enhancement of superconductivity due to an incipient band has long been proposed for multiband Hubbard models on various types of lattices [23,26,36,37,[39][40][41][42][43][44][76][77][78][79][80][81][82]. A salient feature in these cases is that the gap function typically exhibits nodeless "s±-wave" symmetry.…”
Section: Dependence On the Level Offset Between The Two Orbitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superconductivity involving flat bands has also been discussed recently in the context of the flat-band superconductivity 15 , where the virtual pair scattering between the flat and dispersive bands is also at work. The incipient-band-induced superconductivity exploits finiteenergy spin fluctuations, whose importance has recently been noted in other models as well 16 .…”
Section: Introductionmentioning
confidence: 99%